Bacteria Derived from Diamondback Moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), Gut Regurgitant Negatively Regulate Glucose Oxidase-Mediated Anti-Defense Against Host Plant - Qingxuan Qiao; Huiting Feng; Lu Jiao; Uroosa Zaheer; Chanqin Zheng; Li Zhou; Guifang Lin; Xiujuan Xiang; Huang Liao; Shanyu Li; Haiyan Lu; Anyuan Yin; et al. (Insects)
The ongoing interplay among plants, insects, and bacteria underscores the intricate balance of defense mechanisms in ecosystems. Regurgitant bacteria directly/indirectly impact plant immune responses, but the underlying mechanism is unclear. Here, we focus on the interaction between regurgitant bacteria, diamondback moth (DBM), and plant. Six culturable bacteria were isolated from DBM gut regurgitant, including three Enterobacter strains (RB1-3), Micrococcus sp. (RB4), Staphylococcus haemolyticus (RB5), and Bacillus cereus (RB6). These RB strains suppressed genes related to jasmonic acid and glucosinolate signaling pathways but had little effect on salicylic acid signaling pathway genes in Arabidopsis thaliana wounds. RB1 and RB5 inhibited DBM development on A. thaliana but not on an artificial diet. RB1 and RB5 significantly suppressed GOX genes and proteins in DBMs. However, the Pxgox2 insect mutant strain inoculated with RB1 or RB5 did not significantly affect DBM feeding on A. thaliana compared to the wild type. Six RB have been functionally identified, with RB1 and RB5 negatively regulating GOX-mediated host adaptability. The deliberate addition of RB1 and RB5 can negatively affect DBM herbivory and fitness. Our study provides a molecular basis for the further application of RB for insect pest management by modulating insect–plant interactions.